A REVIEW ON THE EXPERIENCES FACED BY ESL TRAINEE TEACHERS DURING TEACHING PRACTICUM - Nur Anisah Tahir; Sangeeth Ramalingam; Ezzan Amnie Azizan; Fairuz Umira Azmi; Nur Ilyani Hadzir; Norashikin Che Pi (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Good and high-quality tertiary education is crucial to ensure that learners can compete globally and achieve high employability. Sustainable Development Goal 4 (SDG 4) emphasizes good quality education where the learners must be equipped with all the necessary skills and abilities needed by the industries. In line with SDG 4, the Ministry of Education of Malaysia also greatly emphasises the ESL students’ skills and competencies. Thus, teaching practicum becomes necessary to produce well-equipped future teachers in learning institutions. Past works of literature revealed mixed perceptions among the teacher trainees’ expectations and the reality they face during their practice. Students often have different expectations from the actual experience. This shows that there is a gap between theory and practice. Additionally, practicum teachers discovered challenges that had huge implications for their teaching performance. Entering a teaching practicum, students are often filled with anticipation and expect to apply their learned strategies in the classroom. Yet the reality often challenges these expectations, showing how complex teaching can be. A review that included previous articles related to teacher trainee experiences revealed an in-depth investigation of their various expectations and realities. Findings based on this review benefit the Ministry of Education, the administrators of universities, and educators in terms of implementing appropriate adjustments for a better practicum experience, particularly for trainee teachers. In conclusion, the contrast between what practicum students expect and what they experience in the classroom highlights the unpredictable nature of teaching. However, these challenges are invaluable for long-term success in education.